REAKTUALISASI NILAI-NILAI KEWIRAUSAHAAN PROFETIK UNTUK MEWUJUDKAN KEMANDIRIAN EKONOMI PESANTREN - Ahmad Fahrurroziqin; Safarotul Jannah; Adi Nur Ali; Muhammad Sidiq Purnomo (An Nuqud Journal of Islamic Economics, 2026)
Economic independence is a crucial factor in ensuring the sustainability and long-term development of Islamic boarding schools (pesantren) amid changing social and economic conditions. This study aims to analyze the reactualization of prophetic entrepreneurship values in promoting the economic independence of pesantren through the management of institutional business units. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis involving business unit managers and other key stakeholders within the pesantren. Data were analyzed through the processes of data reduction, data display, and conclusion drawing. The findings indicate that prophetic entrepreneurship values, including sidq (honesty), amanah (trustworthiness), fathanah (wisdom and competence), tabligh (effective communication), hard work, self-reliance, and a commitment to maslahah (public benefit), are consistently integrated into the management of pesantren business units. The implementation of these values has contributed to improved managerial professionalism, increased stakeholder trust, and more effective utilization of the pesantren's economic resources. The study concludes that prophetic entrepreneurship functions not only as an ethical foundation for business management but also as a strategic approach to strengthening the sustainable economic independence of Islamic boarding schools.